ANALISIS YURIDIS MORATORIUM TERHADAP PEMBERIAN REMISI KEPADA NARAPIDANA TINDAK PIDANA KHUSUS - Fitria Ramadhani Siregar; Alvi Syahrin; Muhammad Ekaputra; Jelly Leviza (USU LAW JOURNAL, 2018)
Abstract The birth of Remission Moratorium Policy as outlined in Government Regulation No. 99 of 2012 has limited the remission to convicts who committed extraordinary crimes, the existence of the moratorium policy is considered as a form of fulfilling the sense of justice of the community who feel has been harmed as a result of the actions of prisoners the. However, the existence of the Regulation is subject to various rejections because it is against the legal norms and principles of human rights. Every prisoner of any crime is entitled to remission, since remission is a basic right for every prisoner without exception, and also one of the efforts in realizing the objective of the penitentiary system that is the guidance of the prisoners in the Penitentiary. This research use normative juridical research method, this research is analytical descriptive by using data collecting method by library research (Library Research), that is by examining secondary data in the form of primary law material like regulation of law, scientific books, journal, papers, articles, etc. Field study (Field Research) through interviews with related parties to serve as supporting or complementary data in conducting research. The results of this study indicate that the underlying remission of all inmates is that remission is a basic right for every prisoner listed in Article 14 Letter i Penal Law. The existence of remission as a supporter of the social reintegration process or reestablish good relations between prisoners and the community. The birth of the moratorium policy of granting remission to prisoners of special crime as outlined in Government Regulation no. 99 Year 2012 is based on the realization of a sense of justice for the community. The Birth of the Policy is expected to create a sense of justice for the people who have been affected due to the impact of extraordinary criminal practices in particular the criminal acts of corruption, narcotics and terrorism. Existence The moratorium policy of granting remission as set forth in Government Regulation No. 99 of 2012 is at a discriminatory value. the regulation does not comply with the norms of law and the principles of human rights.The implementation of the Policy of the  moratorium on remission as set forth in Article 34A Paragraphs 1, 2 and 3 of Government Regulation No. 99 of 2012 must meet the requirements of willing to cooperate in dismantling the criminal case (Justice Collaborator), has paid the fine and replacement money in accordance with the court decision, and has followed the deradicalization program organized by LAPAS. Keywords: moratorium, remission, prisoners, special crimes